2009
DOI: 10.1245/s10434-009-0580-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitivity and Survival in Gastric Cancer Patients with Microsatellite Instability

Abstract: The results of this study indicate that MSI status has no clear influence on overall survival or response to 5-FU in gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
55
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 31 publications
9
55
3
Order By: Relevance
“…Because there is no consensus panel to determine MSI in gastric cancer, MSI phenotype evaluation has been performed using different types of microsatellite sequences. In this study, we used five markers that are accepted as a panel for MSI determination in colon cancer, and the incidence of MSI-H in gastric cancer was 8.5%, which is similar to the results of previous eastern studies (8.2-9.5%) 4,7,8 but lower than those of western studies (16-25.2%). 5,6,11 This difference may be related to the difference in the molecular background of gastric carcinogenesis between eastern and western peoples and may be attributed to different numbers and types of markers used in evaluating the MSI phenotype in gastric cancer.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Because there is no consensus panel to determine MSI in gastric cancer, MSI phenotype evaluation has been performed using different types of microsatellite sequences. In this study, we used five markers that are accepted as a panel for MSI determination in colon cancer, and the incidence of MSI-H in gastric cancer was 8.5%, which is similar to the results of previous eastern studies (8.2-9.5%) 4,7,8 but lower than those of western studies (16-25.2%). 5,6,11 This difference may be related to the difference in the molecular background of gastric carcinogenesis between eastern and western peoples and may be attributed to different numbers and types of markers used in evaluating the MSI phenotype in gastric cancer.…”
Section: Discussionsupporting
confidence: 82%
“…In one study, the usefulness of MSI as a prognostic marker and a predictor of response to adjuvant chemotherapy with 5-FU in 240 gastric cancer patients was evaluated. 7 They showed that there was no survival difference between the MSI-H and MSS/MSI-L groups, and that survival after 5-FU-based chemotherapy did not correlate with MSI status. However, their study was not sufficient to perform multivariate analysis corrected by tumor stage.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, there is a wide variation in results between MSI status and clinicopathological parameters in GCs due to a lack of standardized and comparable parameters (7). Although the potential of MSI as a molecular prognostic marker in GC has gained prominence over the years, most reports in the literature are prone to arbitrariness, and the potential limitations of the National Cancer Institute (NCI)-recommended panel of MS markers for MSI testing have been recognized (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%